Efficacy of reminiscence in cognition, depressive symptoms and quality of life in institutionalized elderly: a systematic review - Isabel Gil; Paulo Costa; Vítor Parola; Daniela Cardoso; Maria Almeida; João Apóstolo (SciELO, 2019)
ABSTRACT Objective: To identify the best available evidence on the efficacy of Reminiscence Therapy in cognition, depressive symptoms and quality of life in elderly individuals with cognitive impairment. Method: The methodology proposed by the Joanna Briggs Institute was used. Studies focused on group Reminiscence Therapy aimed at institutionalized elderly people with cognitive impairment aged 65 or over were considered. The critical analysis, extraction and synthesis of results was performed by two independent researchers. Results: Four randomized clinical trials and two quasi-experimental studies (n=296) were included. Given the heterogeneous characteristics of studies found, it was impossible to perform a meta-analysis. Of the six studies included, two presented statistically significant results for efficacy in cognition, and three for efficacy in reducing depressive symptoms. In none of the studies was evaluated the elderly's quality of life. Conclusion: Reminiscence Therapy has potential efficacy for maintaining cognition and decrease of depressive symptomatology in the target population.